"WELCOME, MY SISTER DEATH!" A Reflection Inspired by St. Francis Experiences of Death - Nadeak, Largus (LOGOS, 2015)
The understanding ofÂ  death varies depending on peoples world views and religious beliefs. The undersanding and the experiences of St. Francis of death is interseting to reflect. He accepted death as a part of human existence, so at the approach of his death he said, â€œWelcome, my sister death!â€ Francisâ€™ view about death was transformed by his experiences of faith and fraternal worldview. Byreflecting death inspired by St. Francisâ€™ experiences of death we prepare ourselves to accept our death. Death is not our enemy, but a part of our human existence. In our death we will rest in peace.